Reconstructing Intersubjective Norms - James Trafford (Rosenberg & Sellier, 2017)
Robert Brandom famously attempts to provide an account of norms that are grounded in intersubjective practices, so dealing with problems raised by Wittgenstein’s regress arguments. This relies upon providing an explanation of the correctness of those practices in terms of our dispositions to treat each other’s practices as correct or incorrect. The view faces a number of hurdles, however, particularly when it comes to providing a non-circular account of the norms of practice, from within those practices themselves. This essay argues that Brandom’s attempt to ground norms in intersubjective practices is circular, and requires communal stability. I go on to suggest that, by taking practices of interaction as foundational, we can ground norms in action coordination. Norms, on this view, become sedimented through our interactions, and explicit normative talk is required to keep our interactions coherent with each other.